The Planetary Theory of Solar Activity Variability: A Review - Scafetta, Nicola; Bianchini, Antonio (Frontiers in Astronomy and Space Sciences, 2022)
Commenting the 11-year sunspot cycle, Wolf (1859, MNRAS 19, 85-86) conjectured that “the variations of spot-frequency depend on the influences of Venus, Earth, Jupiter, and Saturn”. We show that the high synchronization of our planetary system is nicely revealed by the fact that the ratios of the orbital radii of planets obey a highly precise equation. Reviewing the many planetary harmonics and the orbital invariant inequalities that characterize planetary motions from the monthly to the millennial time scales, we show that they are not randomly distributed but clearly tend to cluster around some specific values that also match those of the main solar activity cycles. In some cases, planetary models have even been able to predict the time-phase of solar oscillations including the Schwabe 11-year sunspot cycle. The possibility that solar activity is regulated by its internal dynamics alone has never been able to reproduce the variety of the observed cycles. Although planetary tidal forces are weak, we review a number of mechanisms that could explain how the solar structure and the solar dynamo could get tuned to the planetary motions. In particular, we discuss how the weak tidal forces might be highly amplified in the solar core by an induced increase in H-burning. Mechanisms modulating the electromagnetic and gravitational large-scale structure of the planetary system are also discussed.